Evidence from the 2023 Derna Floods in Libya: Institutional Capability for Disaster Response in Fragile States (Comprehensive Journal of Science, 2026)
In fragile and conflict-affected governments, where governance flaws frequently turn environmental hazards into humanitarian catastrophes, disasters increasingly test the institutional capabilities of these states. This report uses a detailed case study of the 2023 Derna floods to assess Libya's institutional readiness and response capability. Data from documentary sources and semi-structured interviews with frontline rescuers and local officials directly involved in rescue and relief efforts were gathered using a qualitative case study design. The results show that long-standing institutional flaws, such as disjointed governance, deteriorating vital infrastructure, a lack of early warning systems, and poor inter-agency coordination, greatly exacerbated the extent of the destruction in Derna. Despite these limitations, the emergency phase was significantly mitigated by strong community cohesion and outside support. The study comes to the conclusion that proactive institutional transformation, such as unified national coordinating mechanisms, infrastructure governance, responder training, and integrated early warning systems, is necessary to improve catastrophe outcomes in Libya rather than reactive crisis management.
Keywords: Libya, Derna floods, institutional capability, disaster preparedness, fragile states, Response to emergencies